Kai kurių deiktinių žodžių, intensifikatorių ir prieveiksmių kilmės klausimu - Rosinas, Albertas (Baltistica, 1982)
On the origin of some deictic words, intensifying words and adverbs The systematic investigation of the subject in question makes it possible to draw the following conclusions: 1. The deictic words ve, va, vei resp. ave, ava are not reiic forms of the mystic pronouns *vas resp. *avas. In Lithuanian dialects the words ve and vei are reduced from the imperative veiz(d)ėk or veiz(d)i of the verb veiz(d)ėti “to look”, in Latvian vei is reduced from the imperative *vei(z)di resp. ve from veries (cf. vērties “to look”). The variant va has originated from ve in unstressed position. The deictic words ava, ave derive from the interjection a expressing astonishment combined with the words va or ve. The final component -skat of the form anskat “over there” (resp. taskat “there”, šiskat “here”), which is used in East Prussian Lithuanian written records, is a survival of the reduced imperative skatyk of the former verb skatyti(s) “to look”, i. e. an(a) “over there” + skat “look”, cf. anavè ← ana “over there” + vè “look” Geistarai, etc. 2. The initial components ko, ka of the intensifying words kono, kапа are not particles originally, they are genitives of the pronoun kas “who”. The final components -no and -na should be interpreted as an adaptation of the Slavonic nai, cf. Russ. наихудший, Pol. najliepszy to the Lithuanian forms kо and ka. The component ka is reduced from *kā in unstressed position. 3. The components ko resp. to of the adverbs kõtik, konè, niẽko, nekõ as well as the conjunction dėltõ are not particles originally, they are genitives of the pronouns kas and tas.